Estimation of the relationship quality between teachers and students - Tran Thi Trang; Ha Thi Thuy Trang; Le Thi Bich Diep (Journal of Technical Education Science, 2019)
The Relationship Quality between teachers and students plays an important role in educational activities and also affect the emotions and behaviors among them. This article proposes a model with five levels to estimate the Relationship Quality between Teachers and Students based on two following aspects: (1) Identify the agents of the Relationship Quality; (2) The results of the Relationship Quality. In particular, the research will be performed in two phases: Qualitative research through group discussion and Quantitative research based on a survey questionnaires. Therefore, the survey data will be processed using SPSS 20.0 and Amos 20.0 software, in which there will be the participation of many students at Ho Chi Minh City University of Technology. For the effective estimation, the research model will be verified using a structure equation model. The results will show that the Relationship Quality actually affects the overall satisfaction of students, in which factors of “teaching capacity”, “interaction”, “motivation” and “syllabi” have positive effects on the relationship between teachers and students. In addition, the relationship between concepts related to the factors has a difference between groups of sex and school years.